2021
DOI: 10.1073/pnas.2100664118
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the COVID-19 epidemic with nationwide telecommunication data

Abstract: In response to the novel coronavirus disease (COVID-19), governments have introduced severe policy measures with substantial effects on human behavior. Here, we perform a large-scale, spatiotemporal analysis of human mobility during the COVID-19 epidemic. We derive human mobility from anonymized, aggregated telecommunication data in a nationwide setting (Switzerland; 10 February to 26 April 2020), consisting of ∼1.5 billion trips. In comparison to the same time period from 2019, human movement in Switzerland d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 63 publications
2
29
1
Order By: Relevance
“…How effective have lockdowns been at reducing the covid-19 infection and mortality rates? Now that many countries have had more than a year under lockdown, it is possible to study empirically the effectiveness of lockdowns in reducing the spread of covid-19 and the related mortality [ 1 – 5 ]. These lockdowns are non-pharmaceutical interventions of contact among persons within or between populations including restricting travel, closing schools, prohibiting public gatherings, requiring workplace closures, all designed to slow the contagion of the virus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…How effective have lockdowns been at reducing the covid-19 infection and mortality rates? Now that many countries have had more than a year under lockdown, it is possible to study empirically the effectiveness of lockdowns in reducing the spread of covid-19 and the related mortality [ 1 – 5 ]. These lockdowns are non-pharmaceutical interventions of contact among persons within or between populations including restricting travel, closing schools, prohibiting public gatherings, requiring workplace closures, all designed to slow the contagion of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…These lockdowns are non-pharmaceutical interventions of contact among persons within or between populations including restricting travel, closing schools, prohibiting public gatherings, requiring workplace closures, all designed to slow the contagion of the virus. In a recent (published June 2021) large-scale study employing a spatiotemporal analysis of human mobility during the COVID-19 epidemic in Switzerland, it was found that a 1% reduction in human mobility predicted a 0.88 to 1.11% reduction in daily reported COVID-19 cases [ 1 ]. But even as the pandemic has abated in some countries with slowing infection and mortality, it has sped up in some African countries, Columbia, and Brazil [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on data from the first wave of COVID-19, a number of modelling studies provide inconclusive guidance to policy makers. While two publications, one from several countries and one from Switzerland [ 9 , 10 ], concluded that school closures contributed markedly to the reduction of SARS-CoV-2 transmission and individual mobility, respectively, two other studies, one using cross-country data and one from Japan rated school closures among the least effective measures to reduce COVID-19 incidence rates [ 11 , 12 ]. Accordingly, a recent review on SARS-CoV-2 setting-specific transmission rates concluded that there is ‘limited data to explore transmission patterns in […] schools […], highlighting the need for further research in such settings’ [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-reported behavior during the pandemic is expensive to collect and might not be reliable. Conversely, mobile device (i.e., smartphone) location data can be used to quantitatively capture the movement of people [Kishore et al 2020, Persson et al 2021], but they are not well-suited to capturing small social gatherings, which may play a large role in the spread of SARS-CoV-2 [Tupper et al 2020, Whaley et al 2021]. However, digital invitation services can be used to collect data on the size and frequency of social gatherings.…”
Section: Introductionmentioning
confidence: 99%